The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/pr5020019
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Aqueous-Phase Copolymerization of MAA and PEGMA Macromonomer: Influence of Monomer Concentration and Side Chain Length of PEGMA

Abstract: An in situ nuclear magnetic resonance spectroscopy (NMR) technique is used to monitor the aqueous-phase copolymerization kinetics of methacrylic acid (MAA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) macromonomers. In particular, the study analyses the effect of the number of ethylene glycol (EG) groups along the lateral chains of PEGMA and is carried out under fully ionized conditions of MAA at different initial monomer ratios and initial overall monomer concentrations (5-20 wt % in aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Apparently, the microstructure of PCE polymersthe repartition of the polyethylene glycol pendant chains along the mainchainplayed a vital role in their dispersing effectiveness in the AAS system. This statement is supported by previous investigations. Pourchet et al demonstrated that the repartition of the charged anchor groups (MAA) and polyethylene glycol side chains along the mainchain exert a strong impact on the adsorption behavior of PCE polymers on cement particles as well as their subsequent dispersing power. In their work, intrachain composition modification of PCE polymers was achieved via a living/controlled radical polymerization technique (RAFT).…”
Section: Resultssupporting
confidence: 69%
“…Apparently, the microstructure of PCE polymersthe repartition of the polyethylene glycol pendant chains along the mainchainplayed a vital role in their dispersing effectiveness in the AAS system. This statement is supported by previous investigations. Pourchet et al demonstrated that the repartition of the charged anchor groups (MAA) and polyethylene glycol side chains along the mainchain exert a strong impact on the adsorption behavior of PCE polymers on cement particles as well as their subsequent dispersing power. In their work, intrachain composition modification of PCE polymers was achieved via a living/controlled radical polymerization technique (RAFT).…”
Section: Resultssupporting
confidence: 69%
“…One the one hand, the copolymers with short lateral chains (PEGMA 5) were synthesized at neutral pHs, where the reactivity ratios of this pair of monomer is widely different. [ 24 ] Therefore, in order to produce homogeneous composition copolymers the comonomers were fed under starved conditions. [ 25 ] On the other hand, the copolymers with longer lateral chains, those synthesized with macromonomers with higher number of EGu (PEGMA 20, 45, and 113), the copolymerizations were carried out at acidic pH (in this condition r MAA : 1.02, r PEGMA : 1.03), [ 26 ] but starved semibatch operation was also used to maintain the viscosity of the polymerization at manageable values.…”
Section: Resultsmentioning
confidence: 99%
“…Industrially, the most relevant one is the free radical copolymerization (FRC) of methacrylic acid (MAA), acrylic acid or maleic acid with a macromonomer (i.e., poly(ethylene glycol methacrylate), PEGMA) [4]. Alternatively, PCEs are obtained by grafting mono-hydroxylated PEG derivates onto preformed polycarboxylate backbones, such as poly(methacrylic acid) (PMAA) or poly(acrylic acid) (PAA) [4,[28][29][30].…”
Section: Pces In Concretementioning
confidence: 99%
“…Generally speaking, it is difficult to ascribe the dispersity of the grafting density to one particular impact factor during FRC synthesis. The molecular architecture of FRC-PCEs depends on many factors among them the reactivity ratio [29,45] of the comonomers, the monomer feed during synthesis, but also the choice of chain transfer agent or possible side reactions such as radical transfer and termination have to be considered. While the topic deserves further investigation, these results underpin the existence of this inhomogeneity, representing an additional factor that should be considered when studying the working mechanisms of such compounds or seeking to improve their performance.…”
Section: Pces From Free Radical Copolymerizationmentioning
confidence: 99%